Callus induction from the seed of archidendron pauciflorum (jering) / Nuur Hidayatulsyimah Mohd Naser - Mohd Naser, Nuur Hidayatulsyimah (2016)
Archidendron pauciflorum (Jering) is the traditional medical plant from the family of Leguminosae that is native in Southeast Asia. It has been used traditionally to treat a various range of ailments. Genetic improvement is vital in the development of plants in order to increase their yield and quality, however there is no local data on plant tissue culture of Archidendron pauciflorum available. A protocol for successful callus induction from the seed of Archidendron pauciflorum was developed by using the embryo and cotyledon. The explants were inoculated onto Murashige and Skoog (MS) media supplemented with different levels (l.0 - 5.0 mg/L) of 2,4-dichlorophenoxyacetic acid (2,4-D), indole-3-acetic acid (IAA) and naphthalene acetic acid (NAA). After 21 days, compact white callus was obtained from the embryo supplemented with 2 mg/L of 2,4-D and friable white callus from 5 mg/L of NAA and 1 mg/L of IAA. Overall results showed that the presence of 2,4-D is the most suitable auxin to induce the callus on the seed of Archidendron pauciflorum.